Smart: Kritiska perspektiv på smarthetens kulturella praktiker - Nilsson, Fredrik; Sund, Ann-Helen (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2020)
This special issue focuses on the cultural practices of smartness and problematise what might be defined as a cult of smartness. In today’s society, the epithet smart signals development, innovation and sustainability. Smart equals being able to solve various problems and carries a promise of progress and prosperity. One can even talk about a contemporary cult of smartness. Smartness organise and reorganise the relationship between individualcollective; it affects how moral values and identities are negotiated and performed; it intervenes in everyday life and, ideally, allows people to establish new, resilient habits. From a discursive perspective, however, smartness is understood as unstable, conflictual, and in a process of constant becoming. This, in turn, makes smartness a complex web of narratives, and bodily and materialized practices. The articles critically examine such practices in different contexts: street-smart, populist politicians; the conflictual relationship between humans and wolves; seaweed as a smart actor in a sustainable society; the smart home as mundane reality; the micropractices of the homemade; the smart practices of old technologies and; the quest to create smart children through genetic technologies.